Citometria de fluxo como ferramenta na determinação da susceptibilidade antimicrobiana - Anziliero, Eduarda Bassi (2017)
Antimicrobial resistance is a relevant matter to public health. Investments on research and new technologies to evaluate antimicrobial activity are much needed to avoid the surge of new multiresistant strains. Several techniques are available to evaluate antimicrobial activity in vitro in less than 24 h after a positive isolation, allowing to properly choosing the right antibiotic to be used. In this scenario, the development of new methods to quickly and precisely evaluate the antimicrobial susceptibility profile of bacterial isolates would be invaluable for the rational use of antibiotics and, as a consequence, to reduce or even control the surge of bacterial resistance and to prolong patients’ life expectation. Thus, in this study our main goal was to develop a quick protocol to evaluate antimicrobial susceptibility using flow cytometry. We used six antimicrobial drugs, a strain of Escherichia coli (ATCC 25922) susceptible to all antimicrobials, and clinical isolates of E. coli resistant to the same antimicrobial drugs. Prior to testing, the susceptibility profile of all isolates was tested by the disc-diffusion method. The isolates were then cultivated in liquid LB, washed and quantitated by flow cytometry. Standard concentration of antimicrobial drugs were added to 10 4 E. coli cells and incubated for 1, 2 or 3 h at 37ºC. After that, the samples were mixed with propidium iodine (PI) and analyzed by flow cytometry. Viable bacteria were differentiated from unviable in that PI penetrates damaged membranes staining the DNA of death bacteria. As controls to validate this procedure, each bacterial isolate at each indicated time was also collected and seeded on LB agar plate to enumerate the number of viable cells by the classical method and the growing/survival rate was also evaluated in the same samples after incubating for 20h at 36ºC. By using flow cytometry we were able estimate antimicrobial susceptibility in few hours. However, it was not possible to set a positive correlation with plaque counting in that we found a higher percentile of viable cells by flow cytometry. This phenomenon might be explained by the presence of viable but non-cultivable bacterial subpopulations unable to form colonies in agar plates. In the other hand, by using flow cytometry and considering the resistant isolates, we were able to define precisely the resistant characteristics of a given isolate, and this is invaluable for treating infection by multidrug resistant isolates. Thus, we conclude that flow cytometry should be optimized and used as an alternative tool to detect multiresistant bacterial isolates.